(untitled) (Revista Electrónica REDINE, 2018)
The growth reached today by the information and communications technology (ICT) has generated a change in the role of actors in the educational process. Therefore, this study had as intention describe an experience on use of strategies incorporating the ICT to encourage the autonomous work among students in mathematics III of the career civil engineering of the Centroccidental University "Lisandro Alvarado" on issues vectors, coordinates polar geometry of space. A descriptive field study was realized, supported on a documentary investigation. To achieve the goals of the investigation and to obtain the information were in use classroom activities, discussion forum, questionnaires, conceptual maps, infogramas and written tests integrating the ICT. The results show the need to facilitate and strengthen this kind of strategies in the student. It was concluded that to encourage the autonomous work in the student, involves changes both conceptions of teaching as educational practices that promote the participation from the teacher, from the student and from the classmates.